Xanthomonas oryzae Pv. oryzicola Response Regulator VemR Is Co-opted by the Sensor Kinase CheA for Phosphorylation of Multiple Pathogenicity-Related Targets - Cai, Lulu; Ma, Wenxiu; Zou, Lifang; Xu, Xiameng; Xu, Zhengyin; Deng, Chaoying; Qian, Wei; Chen, Xiaobin; Chen, Gongyou (Frontiers in Microbiology, 2022)
Two-component regulatory systems (TCSs) (cognate sensor histidine kinase/response regulator pair, HK/RR) play a crucial role in bacterial adaptation, survival and productive colonization. An atypical orphan single-domain RR VemR was characterized from the nonvascular pathogen Xanthomonas oryzae pv. oryzicola (Xoc) that causes bacterial leaf streak (BLS) disease in rice. Xoc growth and pathogenicity in rice, motility, biosynthesis of extracellular polysaccharide (EPS) and ability to trigger HR in non-host tobacco were severely compromised in the deletion mutant strain R∆vemR as compared to the wild-type strain RS105. Site-directed mutagenesis and phosphotransfer experiments revealed that the conserved aspartate (D56) residue within the stand-alone phosphoacceptor receiver (REC) domain is essential for phosphorelay and the regulatory activity of Xoc VemR. Yeast two-hybrid (Y2H) and co-immunoprecipitation (co-IP) data identified CheA as the HK coopting the RR VemR for phosphorylation. Affinity proteomics identified several downstream VemR-interacting proteins such as 2-oxoglutarate dehydrogenase (OGDH), DNA-binding RR SirA, flagellar basal body P-ring formation protein FlgA, Type 4a pilus retraction ATPase PilT, stress-inducible sensor HK BaeS, septum site-determining protein MinD, cytoskeletal protein CcmA, and Type III and VI secretion system proteins HrpG and Hcp, respectively. Y2H and deletion mutant analyses corroborated that VemR interacted with OGDH, SirA, FlgA and HrpG thus implicating multi-layered control of diverse cellular processes including carbon metabolism, motility and pathogenicity in rice. Physical interaction between VemR and HrpG suggested cross-talk between CheA/VemR- and HpaS/HrpG-mediated signal transduction events orchestrating hrp gene expression.